Effects of exogenous nitrate on repeated sprints with highly trained cross-country skiers in normoxia and normobaric hypoxia - Maycock, A. (Nipissing University, 2023)
The effect of exogenous nitrate (NO3-), ingested as beetroot juice (BRJ), was examined as a potential ergogenic aid for repeated sprint tests (RSTs) in both normoxia (NORM) and hypoxia (HYPO). Low oxygen (O2) availability, whether metabolically or through the environment, may be important for the efficacy of NO3- supplementation because NO3- is reduced to Nitric Oxide (NO) under conditions independent of O2. Eleven male (age = 21 ± 2 years, VO2peak = 68.8 ± 8.2 ml·kg-1·min-1) and 4 female (age = 21 ± 2 years, VO2peak = 58.4 ± 3.5 ml·kg-1·min-1) highly endurance trained cross-country skiers performed RSTs in four conditions: NORM preceded by BRJ; NORM preceded by PLA; HYPO preceded by BRJ; and HYPO preceded by PLA.